Analysis of Preparation and Application of Conductive Polymer Materials - Han Jingwei (MATEC Web of Conferences, 2025)
Conductive polymer materials have evolved into a revolutionary class of functional materials since their discovery, bridging the performance gap between traditional conductive metals and insulating polymers. Their unique combination of tunable electrical conductivity, lightweight nature, flexibility, and processability has driven extensive interdisciplinary research. These materials demonstrate tremendous potential in applications such as flexible electronics, electromagnetic shielding, biomedical applications, among others. Based on the introduction of the conductive mechanisms of conductive polymer materials, this paper categorizes conductive polymer materials into two types: intrinsic conductive polymers and composite conductive polymers. It systematically reviews the preparation methods for both categories. The discussion focuses on the preparation methods of intrinsic conductive polymers containing delocalized large π bonds, as well as the fabrication of composite conductive polymers filled with metals, metal oxides, or nanocarbon materials. The influence of these two types of fillers on the conductive properties of composite polymer materials is critically analyzed. Additionally, the paper investigates and summarizes the applications of conductive polymer materials in three major fields: electronic and electrical materials, biomedical engineering, and environmental protection. Finally, prospects for the future applications of conductive polymer materials are presented.